Use of Electrical Household Appliances and Risk of All Types of Tumours: A Case-Control Study - Shabana Noori; Abdul Aleem; Imrana Niaz Sultan; Afrasiab Khan Tareen; Hayat Ullah; Muhammad Waseem Khan (Medical Sciences, 2025)
Introduction: The use of electrical appliances using extremely low frequency (ELF) electromagnetic fields (EMF) has increased in the past few years. These ELF MF are reported to be linked to several adverse health effects. However, only a couple of studies have been conducted on the association between risk of tumours and use of electronic devices using low frequency (LF) EMF. Methods: We studied the use of common household electrical appliances and suspected risk of tumours in a multi-hospital-based case-control study. In total, 316 patients were included in the final analysis. Results: The study results showed a below unity risk for most of the devices. A slight increased risk of tumour was observed for computer screen use OR: 1.13 (95% CI: 0.43–3.02) and use of microwave oven OR: 1.21 (95% CI: 0.36–4.04). We also had chance to investigate ELF MFs exposure association with tumour. Where we observed elevated odd ratios in individuals living near electricity transformer stations, with a statistically significant risk OR: 2.16 (95% CI: 1.30–3.59). However, the risk was below unity (OR: 0.98) in individuals residing close to powerlines. Conclusion: The current study serves as a pilot study of primary data and will be helpful in future epidemiological research studies on the topic in the region.